Simultaneous right coronary artery spasm in a patient with Anterior ST-Segment Elevation Myocardial Infarction: a case report - Taherpour, Zhiva; Seyedian, Seyed Masoud; Alasti, Mohammad (Novelty in Biomedicine, 2013)
Please cite this article as: Taherpour Z, Seyedian M, Alasti M. Simultaneous right coronary artery spasm in a patient with Anterior ST-Segment Elevation Myocardial Infarction: a case report. Novel Biomed 2013;1:29-33. Simultaneous occlusion of two vessels causing infarction at different territories is an uncommon finding. We report simultaneous right ventricular and anterior ST-segment elevation myocardial infarction in a previously healthy young man. The angiographic results demonstrated the simultaneous occlusion of the right and left coronary arteries because of simultaneous occlusion of left anterior descending artery (LADA) and spasm of right coronary artery (RCA). In this patient, we found simultaneous ST elevations in right and precordial leads so everyone should be careful about all leads of the surface electrocardiogram for decision making in the management of a patient.